Experimental Mechanics on Emerging Energy Systems and Materials, Volume 5 Proceedings of the 2010 Annual Conference on Experimental and Applied Mechanics - Proulx, Tom.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
This the fifth volume of six from the Annual Conference of the Society for Experimental Mechanics, 2010, brings together 25 chapters on Emerging Energy Systems. It presents early findings from experimental and computational investigations including Material State Changes in Heterogeneous Materials for Energy Systems, Characterization of Carbon Nanotube Foam for Improved Gas Storage Capability, Thermoresponsive Microcapsules for Autonomic Lithium-ion Battery Shutdown, Service Life Prediction of Seal in PEM Fuel Cells, and Assessing Durability of Elastomeric Seals for Fuel Cell Applications.
Keywords: Engineering; Mechanics; Mechanics, applied; Materials; Engineering; Theoretical and Applied Mechanics; Mechanics; Materials Science, general